Development of cladding oxidation analysis code [COAC] and application for early stage severe accident simulation of AP1000. (November 2015) - Mao, Keyou; Wang, Jun; Li, Longze; Zhang, Yapei; Tian, Wenxi; Su, Guanghui; Qiu, Suizheng; Corradini, Michael L.
Abstract: Clad oxidation is an important phenomenon which can affect core degradation under severe accident conditions. The oxidation process always coincides with cladding material embrittlement. The energy released from the oxidation of cladding material can accelerate the accident process, and the hydrogen released from oxidation may threaten the integrity of vessel. As a consequence, the high temperature clad solid-phase oxidation model research and its code development play an important role in reactor safety analysis. To push the research on this region, a clad solid-phase oxidation analysis code (COAC) is developed by Xi'an Jiaotong University. To verify the quality of COAC, CORA-13 is used as a benchmark. The results show that COAC does produce expected values. COAC is then applied to AP1000 severe accident calculations. In this case, the station blackout accident (SBO) is modeled. The response of fuel rods under varying natural circulation conditions while coolant pump idle time is calculated. The calculations show that the oxidation of cladding can delay fracturing, and protect its integrity. Meanwhile, the performances of other oxidation models are explored in this paper. Highlights: Clad solid-phase oxidation analysis code (COAC) is developed. Early state severe accident simulation of AP1000 is made. Temperature distribution and hydrogen generation rate are calculated.